Hubungan Pengetahuan Terkait Label Pangan dengan Sikap dan Kepatuhan Membaca Label pada Kelompok Usia Produktif di Indonesia - Dwijayanti, Isniati; Dwi Juliani, Kurnia (Kabar Gizi Indonesia, 2024)
Reading food labels is one of the important messages from the Balanced Nutrition Guide. It is suggested to influence the attitude and behavior in buying packaged food that is consumed. This research study analyzed the relationship between knowledge regarding food labels and attitude and compliance with food label reading among productive age groups in Indonesia. The research design was a narrative literature review from many databases including Google Scholar, Portal Garuda, DOAJ, and Pubmed in the last five years (May 2019 – May 2024). The number of 2603 articles from databases were gotten and then would selected based on inclusion criteria such as cross-sectional study paper, age ranged 15-29 years old, high school or university students, located in Indonesia, and provided the correlation between knowledge with attitude and compliance. There were 7 articles selected, including 2 articles regarding the correlation between knowledge and attitude, and 5 articles regarding the correlation between knowledge and compliance. This study concluded that there was a significance correlation between knowledge and attitude but there was no significant correlation between knowledge and compliance in food label reading.